Rat exposure in mice with neuropathic pain induces fear and antinociception that is not reversed by 5-HT2C receptor activation in the dorsal periaqueductal gray - Furuya-da-Cunha, Elke Mayumi [UNESP] (2016)
Previous studies have demonstrated that serotonin 5-HT2C receptors in the dorsal periaqueductal gray (dPAG) mediate both anxiety and antinociception in mice submitted to the elevated plus maze. The present study examined the effects of intra-dPAG infusion of the serotonin 5-HT2C receptor agonist (MK-212) in the defensive reactions and antinociception in mice with neurophatic pain confronted by a predator. Neuropathic pain was induced by chronic constriction injury (CCI) of the sciatic nerve, and predator confrontation was performed using the rat exposure test (RET). Our results demonstrated that both sham-operated and CCI mice exhibited intense defensive reactions when confronted by rats. However, rat-exposed CCI mice showed reduced pain reactivity in comparison to CCI mice exposed to a toy rat. Intra-dPAG infusion of MK-212 prior to predator exposure did not significantly alter defensive or antinociceptive responses. To our knowledge, our results represent the first evidence of RET-induced antinociception in mice. Moreover, the results of the present study suggest that 5-HT2C receptor activation in the dPAG is not critically involved in the control of predator-evoked fearful or antinociceptive responses.